Comparing the efficacy ultrasound guided bilateral transversus abdominis plane (TAP) block between 0.25% bupivacaine versus 0.125% bupivacaine in laparoscopic appendicectomy - Zulkipeli, Zubaidah (2017)
Acute appendicitis is a common cause acute surgical abdomenl. Laparoscopic appendicectomy becames more common practise nowadays as compare to open appendicectomy. Transversus abdominis plane (TAP) block is a proven beneficial for post-operative pain control in lower abdominal surgery including laparoscopic surgery. However, more studies are needed to determine effective optimum dose required for post-operative pain control in laparoscopic surgery. This study was aimed to determine the efficacy of 0.125% bupivacaine as compare to standard dose 0.25% bupivacaine in ultrasound guided bilateral transversus abdominis plane (TAP) block for post-operative pain control in laparoscopic appendicectomy. Method This study was a prospective, double blinded and randomized controlled trial involving patients came for emergency laparoscopic appendicectomy. Participants were randomized into two groups by using computer assisted randomization. Group 1 received ultrasound guided transversus abdominis plane (TAP) block using 0.25% bupivacaine whereas group 2 received 0.125% bupivacaine immediately after the operation finished. The visual analogue pain score (VAS) were assessed at 30 minutes, 4H, 8H, 16H and 24H post operation. Total PCA fentanyl requirement were compared between these two groups. Complication from the laparoscopic surgery and TAP block was documented. Result Overall visual analogue pain score was comparable between these two groups. The overall mean difference in Visual Analogue pain Score(VAS) was 0.58 {(95% CI -0.17,3.12), p value=0.128. Mean difference of VAS at 1/2H, 4H, 8H, 12H, 16H and 20H comparable between these 2 groups which were 0.18(n=44), 0.68(n=44), 0.86(n=44), 0.06(n=40), 0.31(n=28) and 0.38(n=19) respectively. The total PCA fentanyl requirement between both groups were insignificant (132.95mcg vs 128.64mcg) (MD:4.32, p value = 0.73). No complication arises from TAP block. Conclusion Ultrasound guided bilateral TAP blocks for post-operative pain control in laparoscopic appendectomy using 0.125% bupivacaine is as effective as 0.25%. Lower concentrations of local anaesthetic reduce risk of toxicity and cost while providing similar post operative analgesia quality. Ultrasound guided TAP block is considered effective and safe with a proper technique. Oral analgesia should be started as soon as possible to prevent breakthrough pain.